Out of my life and thought : an autobiography - Schweitzer, Albert, 1875-1965. (New York : H. Holt, 1990)
Memoirs of the doctor who won the 1952 Nobel Peace Prize, describing his career.
Translation of: Aus meinem Leben und Denken.
Includes bibliographical references (p. 257-260) and index.
Keywords: Schweitzer, Albert, -- 1875-1965.; Strasbourg (France) -- Biography; Missionaries, Medical -- Gabon -- v; Theologians -- Europe -- Biography; Musicians -- Europe -- Biography